Systematic review of ocular surface treatments in the setting of thyroid eye disease - Wong, Anthony Stephen; Chelnis, James G. (Frontiers in Ophthalmology, 2024)
IntroductionApproximately 85% of patients with thyroid eye disease experience ocular surface symptoms. Although corneal exposure plays a role in inducing inflammatory changes to the ocular surface, multiple studies reveal more complexity to the abnormal tear film composition and parameters in thyroid eye disease patients including those who do not have proptosis or increased corneal exposure. Currently, a majority of cases of thyroid associated dry eye symptoms are given treatments intended for ocular surface disease arising from different etiologies. MethodsMedline via Ovid, Cochrane CENTRAL, PubMed, and Google Scholar were systematically searched for articles evaluating the efficacy of treatments for dry eye symptoms in patients with thyroid eye disease. Articles were from all geographic regions and dates ranged from inception until October 2023. ResultsSeven papers ultimately met inclusion criteria and were included in this review. These papers revealed that multiple topical and non-topical treatment modalities address dry eye symptoms in thyroid eye disease and improve subjective and objective ocular surface parameters. However, due to the few studies that exist and due to disparities in sample size and study design, no overwhelming best practices were identified that could influence clinical practice.ConclusionThis systematic review identifies the current treatments that exist and highlights the clear unmet need for a large population suffering with dry eye symptoms. Ideally, further well-designed investigations into this area would target topical, non-invasive modalities to develop first line options for thyroid eye disease patients.